Estructura celular del xilema de la rama para establecer una metodología de caracterización tecnológica del tronco de árboles en áreas naturales protegidas - Valderrama Freyre, Heiter (2008)
A methodology based on the knowledge of the cell structure of xylem of branches of 10 cm diameter for technological characterization of wood from tree stem is proposed in this research, which can be used in forest species from natural protected areas without felling down the whole tree. Data were gathered from trees of ten forest species belonging to the “Arboretum Jardín Botánico” of the National University of the Peruvian Amazon; description of cell structure was carried out in the laboratory. Relevant identification characteristics were found; among them, forked fibers in Cedrelinga cateniformis, some stratification of fibers in longitudinal sections in Tapirira guianensis, Chrysophyullum sanguinolentum and Simaruba amara, transverse septa in fibers in Leonia glicycarpa, and crystals in some axial parenchyma cells of Caryocar glabrum. The comparative analysis of stem cells versus branch cells of studied species allowed identification of 20 qualitative and quantitative characteristics useful for inferring stem wood behavior in relation to drying, preservation, mechanical strength, natural durability, workability and pulp and paper making; these characteristics all together form the proposed methodology.